Kebijakan Pemerintah di Bidang Penanaman Modal Asing (PMA) dalam rangka Meningkatkan Iklim Investasi di Indonesia (Lex Jurnalica, 2010)
In a planned development inIndonesiacan be said to be a new beginning since the New Order, set out in each Repelita. National development is a conscious effort throughout the nation to raise the dignity that is parallel with the other nations in the world. Implementation of development itself not only requires the availability of capital development in terms of availability of natural resources, but also requires the availability of the other capitals in the form of skills, technology management capabilities, noted that financial and others. In the early stages of development, it is felt that the ability of the Indonesian nation has not been sufficient to carry out the development independently. Limitations of technology, skills and abilities as well as financial management becomes a serious obstacle in the implementation of development. To overcome these obstacles, the government invited foreign capital to invest inIndonesia.Keywords: Development, Investation, Government